Investigation of the optimal position of wind sensors and wind turbines on a building: A computational fluid dynamics study - Chan L.; Mohd Roslan M.E.B.; Mohamed H.B. (Institute of Advanced Engineering and Science, 2023)
Most numerical studies on flow over buildings simplify the geometry of the roof and assume that it is flat. This may lead to misrepresentation of the flow as the roof of actual buildings contains some sort of roughness. In this study, the flow over the administrative building of Universiti Tenaga Nasional is investigated for multidirectional flow conditions. The actual topology of the building is gridded and simulated using the steady-state Reynolds-averaged Navier-Stokes equation. Four points at the top of the building are identified and the wind statistics at these designated locations at three different heights are investigated. The optimal location with the highest average wind speed and consistent wind speeds for all wind angles is identified and is earmarked as a potential location to install the wind turbine. 2017 Institute of Advanced Engineering and Science. All rights reserved.